2016
DOI: 10.1007/s11916-016-0581-9
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Treatment of Migraine: Risk Factors and Behavioral Issues

Abstract: Migraine can impact every aspect of a person's functioning. Psychological comorbidities, cognitive constructs, and behavioral responses to pain greatly impact the perception of migraine pain, treatment efficacy and outcome, and overall quality of life and functioning. Current considerations for migraine treatment emphasize the utility of the biopsychosocial model in understanding and treating migraine, noting both the importance of addressing psychological factors such as cognitive beliefs as well as psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Over 90% of the migraineurs had prescriptions for acute treatment of their migraines, of which most prescriptions were for triptans. Opioids were prescribed for acute migraine treatment nearly twice as frequently for chronic migraineurs, and nearly one in four of these patients had medication‐overuse headaches, which may have been due to the use of opioids . Medication‐overuse headaches and the use of opioids for acute migraine therapy, after a trial of non‐opioid treatment, indicates poor coping capacities in patients for managing migraine pain and the need for more efficacious treatments for this neurologic disease …”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of the migraineurs had prescriptions for acute treatment of their migraines, of which most prescriptions were for triptans. Opioids were prescribed for acute migraine treatment nearly twice as frequently for chronic migraineurs, and nearly one in four of these patients had medication‐overuse headaches, which may have been due to the use of opioids . Medication‐overuse headaches and the use of opioids for acute migraine therapy, after a trial of non‐opioid treatment, indicates poor coping capacities in patients for managing migraine pain and the need for more efficacious treatments for this neurologic disease …”
Section: Discussionmentioning
confidence: 99%
“…[ 9 11 ] In the treatment of migraine, analgesic-based interventions are the most commonly used therapies and include drugs such as ibuprofen and opioids; however, with ongoing clinical observation, the efficacy of these classes of drugs and their side effects have raised questions and concerns. [ 12 , 13 ] Long-term clinical practice has confirmed that cutting therapy, as a complementary alternative therapy, has shown good results in the treatment of migraine. This therapy is a new application based on the guidance of the theory of acupuncture and moxibustion acupoints in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that sleep disorders, anxiety, depressive states, and estrogen levels are closely related to the occurrence of this disease [9–11] . In the treatment of migraine, analgesic-based interventions are the most commonly used therapies and include drugs such as ibuprofen and opioids; however, with ongoing clinical observation, the efficacy of these classes of drugs and their side effects have raised questions and concerns [12,13] . Long-term clinical practice has confirmed that cutting therapy, as a complementary alternative therapy, has shown good results in the treatment of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add further evidence to the efficacy and safety profile of triptans contrasted to opioids, and reinforces the opportunity to avoid them in the management of migraine, because chronic opioid therapy in migraineurs is associated to worse disability and QoL and to psychiatric comorbidity. 37,38 To address whether the rate of comorbidities and multimorbidity different from the general population of Italian adults, we compared the results from our sample to that of three different population studies. The first study described the association between overweight, obesity, and the presence of selected comorbidities 39 ; the second was on the premature onset of age-related comorbidities among HIV-infected and noninfected general population 40 ; the third was on the burden of multimorbidity in relation to age, gender, and immigrant status.…”
Section: Discussionmentioning
confidence: 99%